menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
In the following equation solve for t, 2t-s=p
asked
Jul 18, 2019
184k
views
2
votes
In the following equation solve for t, 2t-s=p
Mathematics
college
FoxDeploy
asked
by
FoxDeploy
6.0k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
4
votes
2t-s=p
+s +s
2t=p+s
—- —-
2 2
T= (p+s)/2
Alex Chi
answered
Jul 20, 2019
by
Alex Chi
5.7k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
6
votes
2t-s=p Add
2t=p+s Divide
t=
Blem
answered
Jul 25, 2019
by
Blem
5.0k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
6.2m
questions
8.2m
answers
Other Questions
Solve using square root or factoring method plz help!!!!.....must click on pic to see the whole problem
giles is searching for a sock and discovers that he has 10 socks for every 5 pairs of shoes. if he has 20 socks how many pair of shoes does he have
Hiroto’s texting plan costs $20 per month, plus $0.05 per text message that is sent or received. Emilia’s plan costs $10 per month and $0.25 per text. Using the graph below, which statement is true? A)
WILL UPVOTE EVERY ANSWER! MULTIPLE CHOICE! Solve for Y. 8-8y=2y+78 A)y=7 B)y=70 C)y=-7 D)y=-70
Can someone help ?? I wasn't here for the lesson
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org